Berudu (Amphibia: Anura) di Taman Wisata Air Terjun (TWAT) Kembang Soka, Kulon Progo, Daerah Istimewa Yogyakarta Pada Musim Kemarau - Nishfi Laila Maghfiroh; Rury Eprilurahman (Jurusan Biologi FMIPA Universitas Cenderawasih, 2019)
Kembang Soka Waterfall Tourism Park in Java, Indonesia, is a potential habitat for frogs and toads (Anurans), as it contains a wide variety of water sources. To date, research on the diversity of Anura in the park has been limited to adult individuals. As such, the diversity of larvae is unknown. This study aimed to determine the diversity of Anuran tadpoles and their habitat in Kembang Soka Waterfall Tourism Park. Several surveys were carried out during the dry season of July–October 2018, with a total of five breeding sites surveyed. Three species of tadpoles were recorded: Leptobrachium hasseltii, Limnonectes kuhlii, and Phrynoidis aspera. The tadpoles of L. hasseltii had the greatest abundance, and were found in almost all breeding sites. Conversely, the tadpoles of L. kuhlii and P. aspera were only found in two of the breeding sites. Key words: tadpoles, diversity, dry season, Kembang Soka Waterfall Tourism Park.